De novo transcriptome analysis of immune response on cobia (Rachycentron canadum) infected with Photobacterium damselae subsp. piscicida revealed inhibition of complement components and involvement of MyD88-independent pathway. Issue 77 (June 2018) - Tran, Hung Bao; Lee, Yen-Hung; Guo, Jiin-Ju; Cheng, Ta-Chih
Abstract: Cobia, Rachycentron canadum, one of the most important aquatic species in Taiwan, has suffered heavy losses from Photobacterium damselae subsp. piscicida, which is the causal agent of photobacteriosis. In this study, the transcriptomic profiles of livers and spleens from Pdp-infected and non-infected cobia were obtained for the first time by Illumina-based paired-end sequencing method with a focus on immune-related genes. In total, 164, 882 high quality unigenes were obtained in four libraries. Following Pdp infection, 7302 differentially expressed unigenes from liver and 8600 differentially expressed unigenes from spleen were identified. Twenty-seven of the differently expressed genes were further validated by RT-qPCR (average correlation coefficient 0.839, p -value <0.01). Results indicated a negative regulation of complement components and increased expression of genes involved in MyD88-independent pathway. Moreover, a remarkable finding was the increased expression of IL-10, implying an inadequacy of immune responses. This study not only characterized several putative immune pathways, but also provided a better understanding of the molecular responses to photobacteriosis in cobia. Highlights: The first transcriptome in cobia was de novo assembled and analyzed. Early immune responses were monitored by transcriptomic profiling of liver and spleen. Anti-inflammatory expression and complement inhibition were mainly observed. MyD88-independent pathway could be involved in immune response against Pdp.